Assessing psychometric of Malaysian version of school leaders transformational leadership instrument - Mohammed Afandi Zainal,; Mohd Effendi @ Ewan Mohd Matore,; Wan Norshuhadah W Musa, (Penerbit Universiti Kebangsaan Malaysia, 2022)
The purpose of the study is to analyse the psychometric properties of a survey questionnaire, Malaysian Version of School Leaders Transformational Leadership Instrument (MvTL) using Rasch Measurement Model aided by Winstep software Version 3.73. The questionnaire was administered on 109 school teachers from Melaka. The data were analyses to examine the items functional accordingly from the aspect of items fit in measuring constructs, items polarity, unidimensionality, local independence and the reliability and separation of item and respondent. The Rasch analysis showed satisfying psychometric properties of MvTL after removal of some misfitting items. Fit statistic evaluation discovered that a sum of 5 items were out of range and leaving only 20 items remaining that are appropriate to measure the four constructs of the transformational leadership among school leaders in the MvTL. Further analysis with the remaining 20 items revealed that each PTMEA Corr is in positive values and met the assumptions of unidimensionality and local independence. Reliability and separation index were also within acceptable range. As for future research, it is recommended that different studies should be organized by using a bigger scope and various samples to generate a much better, detailed and comprehensive information which can be represented more extensively.